2023
DOI: 10.1093/ehjcvp/pvad086
|View full text |Cite
|
Sign up to set email alerts
|

New-onset syncope in diabetic patients treated with sodium-glucose cotransporter-2 inhibitors versus dipeptidyl peptidase-4 inhibitors: a Chinese population-based cohort study

Xinyi Gao,
Nan Zhang,
Lei Lu
et al.

Abstract: Background and Aims Syncope is a symptom posing an important diagnostic and therapeutic challenge, and generate significant cost for the healthcare system. Sodium-glucose cotransporter-2 inhibitor (SGLT2i) have demonstrated beneficial cardiovascular effects, but their possible effects on incident syncope have not been fully investigated. This study compared the effects between SGLT2i and dipeptidyl peptidase-4 inhibitor (DPP4i) on new-onset syncope. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The system has been used by local teams in Hong Kong to conduct comparative studies. [13][14][15] The exclusion criteria of the study involved patients: 1) With prior NPC or H&N cancer 2) Without complete demographics 3) Under 18 years old (Figure 1). This study employed an as-treat approach, including the censoring of patients at the discontinuation of treatment or switching between the comparison medications.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…The system has been used by local teams in Hong Kong to conduct comparative studies. [13][14][15] The exclusion criteria of the study involved patients: 1) With prior NPC or H&N cancer 2) Without complete demographics 3) Under 18 years old (Figure 1). This study employed an as-treat approach, including the censoring of patients at the discontinuation of treatment or switching between the comparison medications.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…CDARS encodes diagnoses using the International Classification of Diseases, ninth revision (ICD-9), as CDARS has not implemented ICD-10 codes to date. 9 Mortality data were acquired from the linked Hong Kong Death Registry, a governmental registry of mortality data for Hong Kong citizens. CDARS and the linked Hong Kong Death Registry have been used extensively in research, with good coding accuracy and data completeness as demonstrated in previous studies.…”
Section: Data Sourcementioning
confidence: 99%